2014
DOI: 10.1002/aenm.201401259
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Morphology of High Efficiency Polymer Solar Cells Based on the Donor Polymer PBDTTT‐EFT

Abstract: advantages, such as solution processability, low cost, and fl exibility. The invention of the bulk heterojunction (BHJ) architecture is regarded as a milestone in the history of OPV. [ 3,4 ] The BHJ architecture consists of nanoscale interpenetrating networks of donor and acceptor phases with phase separation close to the exciton diffusion length (≈10 nm). [ 5 ] The interfacial area between donor and acceptor materials is increased by several orders of magnitude compared to the bilayer architecture resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
124
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 43 publications
10
124
0
Order By: Relevance
“…It has been shown that the surface of a PBDTTT-EFT:PC 71 BM blend film is slightly enriched by the polymer component (containing around 60% of PBDTTT-EFT), and that PC 71 BM aggregation is suppressed due to the presence of DIO during solution casting. [15] For this reason we conclude that the surface structure observed here is unlikely to originate from coarse-scale phase-separation between the polymer and the fullerene.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…It has been shown that the surface of a PBDTTT-EFT:PC 71 BM blend film is slightly enriched by the polymer component (containing around 60% of PBDTTT-EFT), and that PC 71 BM aggregation is suppressed due to the presence of DIO during solution casting. [15] For this reason we conclude that the surface structure observed here is unlikely to originate from coarse-scale phase-separation between the polymer and the fullerene.…”
mentioning
confidence: 64%
“…[7,8] The design and synthesis of new conjugated polymers has been one of the main drivers in the improvement of OPV efficiency, with polymers based on benzodithiophene (BDT) attracting significant research interest. [9][10][11][12][13][14] Recently, a new polymer,poly [4,8- [15,16]. Notably, such PBDTTT-EFT based devices have been fabricated using spin-coating in a nitrogen-filled glove box.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 57,58 ] For instance, Xiao et al [ 55 ] used a comprehensive set of characterization techniques including small-angle neutron/X-ray scattering and neutron refl ectometry to reveal the impact of DIO on the PBDTTT-C-T:PC 71 BM morphology from the cast solution to the solid fi lm; they found that DIO is critical for enhancing wileyonlinelibrary.com crystallinity and strongly improving both lateral and vertical phase segregation in the fi lm solidifi cation stage (see Figure 5 ). Our group and collaborators demonstrated that DIO is helpful to optimize surface composition distributions of PBDTTT-C-T:PC 71 BM fi lm close to electrodes, enabling a fullerene-rich composition near the cathode interface that enhances charge extraction of inverted OPVs.…”
Section: Understanding Of the Morphology Of Opvs Featuring Well-knownmentioning
confidence: 98%
“…GIWAXS measurements were collected at the SAXS/WAXS beamline at the Australian Synchrotron, with a setup similar to our previously reported studies. [ 32,45 ] The energy of X-ray incident beam was fi xed at 14 KeV with an incident angle of 0.4°. 2D scattering patterns were collected using a Dectris Pilatus 1 M detector with a total exposure time of 3 s. The sample was moved to a new spot after each scan to avoid beam damage.…”
Section: Methodsmentioning
confidence: 99%